Resveratrol induces cell cycle arrest and apoptosis in epithelioid malignant pleural mesothelioma cells - BATIREL, HASAN FEVZİ; BATIREL, SAİME (WALTER DE GRUYTER GMBH, 2018)
Background: Resveratrol is a natural anti-carcinogenic polyphenol. Malignant pleural mesothelioma (MPM) is an aggressive tumor with poor prognosis. In this study, we investigated the effects of resveratrol on epithelioid MPM. Material and methods: Human epithelioid MPM cell line (NCI-H2452) was exposed to resveratrol (5-200 mu M) for 24 or 48 h. Cell viability was assessed by WST-1 assay. Flow cytometry analyses were performed to evaluate the effects of resveratrol on cell cycle distribution and apoptosis. Western blot analysis was used to determine protein expression levels of antioxidant enzymes, cyclin D1 and p53. Reactive oxygen species (ROS) were measured using H2 DCFDA. Results: Resveratrol reduced cell viability of the cells in a concentration and time dependent manner. After treatment, the cells accumulated in G0/G1 phase and the percentage of cells in G2/M phase was reduced. Resveratrol decreased cyclin D1 and increased p53 expression in cell lysates. Treated cells exhibited increased apoptotic activity. ROS were elevated with resveratrol treatment, but there was no change in the expression of superoxide dismutase (SOD)-1, SOD-2 and glutathione peroxidase. Conclusion: Our results revealed that resveratrol exhibits anti-cell viability effect on epithelioid MPM cells by inducing cell cycle arrest and apoptosis. Resveratrol may become a potential therapeutic agent for epithelioid MPM.
Keywords: Resveratrol; Malignant pleural mesothelioma; Oxidative stress; Apoptosis; Cell cycle; ANTIOXIDANT ENZYMES; GROWTH-INHIBITION; CANCER-CELLS; CLOFARABINE; EXPRESSION; PROTEIN-1; D1